PIRAMIDA CARROLL PADA PERUSAHAAAN DI INDONESIA : STUDI PADA 3 PERUSAHAAN PEMENANG CSR AWARD 2016 - Temy Setiawan; Ari Purwanti (JMB : Jurnal Manajemen dan Bisnis, 2017)
Currently, CSR disclosure to stakeholders in Indonesia has been done by many companies. Such disclosures are integrated in the annual report or produced as a report. Many motives underlie the disclosures. The purpose of this study is to describe the company's profile and CSR disclosure motives of the winning company of CSR Award Indonesia 2016 in accordance with the Carroll pyramid. Company’s disclosures will be analysed using the 10 principles developed by the United National Global Compact (UNGC). This study will analyses the data of the three companies who won CSR Award Indonesia 2016 from 2011 to 2015 using the corresponding indicators which are in accordance to the 10 principles of UNGC. The source of data are financial reports and sustainability reports. Findings. The analyses on the three companies that become the object of analysis has disclosed sustainability information that is in accordance with the 10 principles of UNGC. When associated with the CSR disclosure motive based on Carroll pyramid, the company has economic, legal, and ethical motives. Philanthropicic motive is not much expressed. Another finding shows that the three companies being analysed are engaged in mining and automotive.Saat ini pengungkapan CSR di Indonesia kepada pemangku kepentingan sudah mulai banyak dilakukan oleh perusahaan baik terintegrasi di dalam laporan tahunan maupun dalam laporan tersendiri. Banyak motif yang mendasari pengungkapan tersebut. Tujuan dari penelitian ini untuk mendeskripsikan prodil perusahaan dan motif pengungkapan CSR dari perusahaan pemenang CSR Award Indonesia 2016 sesuai dengan piramida Carroll. Pengungkapan perusahaan akan dianalisis dengan 10 prinsip yang dikembangkan oleh United National Global Compact (UNGC). Penelitian ini akan menganalisis 3 perusahaan pemenang CSR Award Indonesia 2016 dari tahun 2011 hingga 2015 dengan indikator yang sesuai 10 prinsip UNGC. Sumber data adalah laporan keuangan dan sustainability report. Tiga perusahaan yang merupakan objek analisis mengungkapkan informasi keberlanjutan sesuai dengan 10 prinsip UNGC. Apabila dikaitkan dengan motif pengungkapan CSR pada piramida Carroll, perusahaan tersebut memiliki motif secara ekonomi, legal dan etika. Motif filantropi tidak banyak diungkapkan. Temuan lainnya, tiga perusahaan yang dianalisis bergerak di bidang tambang dan otomotif.